Knowledge Management Infrastructure on Organizational Performance in Indonesian Science Institutions (LIPI): Mediation Effects of Knowledge Management Process - Indah Smaradhani, Ika; Vitayala Sjafri Hubeis, Aida; Syarief Hidayatulloh, Furqon (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
As a research institution, the Indonesian Institute of Sciences (LIPI) plays a crucial role in driving innovation and leveraging knowledge to improve people's welfare and the nation's competitiveness. This study analyzes the impact of knowledge management on the performance of science and technology correctional-based organizations at LIPI. This study aims to determine the relationship between knowledge management, including knowledge management infrastructure and processes, and organizational performance. The sample used in this study were employees responsible for the dissemination of science and technology in five service work units at LIPI, with a total of 115 respondents. The analytical method utilized in this study is a quantitative method using SEM PLS. The results of this study demonstrates that: (1) There is a significantly positive relationship between knowledge management infrastructure and knowledge management process; (2) There is a significantly positive effect in the relationship between knowledge management infrastructure and organizational performance; (3) There is a positive and significant relationship between knowledge management process and organizational performance; and (4) The knowledge management process mediates the relationship between knowledge management infrastructure and organizational performance. The results indicated that the science and technology correctional service-based work unit at LIPI have implemented knowledge management practices well in terms of infrastructure and processes. However, there is still room for improvement in certain areas. Keywords: knowledge management process, knowledge management infrastructure, organizational performance, research institution, sem pls